2016
DOI: 10.1161/circoutcomes.115.002436
|View full text |Cite
|
Sign up to set email alerts
|

Is Isolated Low High-Density Lipoprotein Cholesterol a Cardiovascular Disease Risk Factor?

Abstract: Background While the inverse association between high-density lipoprotein cholesterol (HDL-C) and risk of (CVD) has been long established, it remains unclear whether low HDL-C remains a CVD risk factor when levels of low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG) are not elevated. This is a timely issue because recent studies have questioned whether HDL-C is truly an independent predictor of CVD. Methods and Results 3590 men and women from the Framingham Heart Study offspring cohort witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 48 publications
3
44
0
2
Order By: Relevance
“…Definite reason is unclear, but coronary lesion in females is likely to be affected by dyslipidemia. In addition, this study also indicated that the combination of LDL-C and HDL-C is more useful than HDL-C alone for predicting the development of MACEs in females, consistent with the results of the Framingham Heart Study [24] that comprehensive assessment using multiple parameters including HDL-C was important for managing the risk of CAD. Although it is ideal in theory for both LDL-C and HDL-C to have reached their respective target control levels by the time of PCI in both males and females, the incidence of MACEs in females was lower when either LDL-C or HDL-C reached its target level than when neither did so.…”
Section: Discussionsupporting
confidence: 84%
“…Definite reason is unclear, but coronary lesion in females is likely to be affected by dyslipidemia. In addition, this study also indicated that the combination of LDL-C and HDL-C is more useful than HDL-C alone for predicting the development of MACEs in females, consistent with the results of the Framingham Heart Study [24] that comprehensive assessment using multiple parameters including HDL-C was important for managing the risk of CAD. Although it is ideal in theory for both LDL-C and HDL-C to have reached their respective target control levels by the time of PCI in both males and females, the incidence of MACEs in females was lower when either LDL-C or HDL-C reached its target level than when neither did so.…”
Section: Discussionsupporting
confidence: 84%
“…Low HDL levels predict increased cardiovascular risk, while high HDL levels are associated with a drop of up to 40% in cardiovascular risk compared to low HDL alone; that is to say, when HDL levels are below the recommended levels, there is risk of complications, especially of cardiac nature 21 - 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the reality is more complex than this. Recent work indicates that the context in which HDL levels occur ( i.e ., levels of LDL and triglycerides) influences the utility of HDL as a predictor of cardiovascular disease risk (9). Furthermore, specific subspecies of each of the lipoprotein classes appear to be more relevant to cardiovascular disease prediction than others.…”
Section: Sex Differences In Obesity Co-morbiditiesmentioning
confidence: 99%